Thyroid control of sarcolemmal Na+/Ca2+ exchanger and SR Ca2+-ATPase in developing rat heart - Cernohorský, J; Kolár, F; Pelouch, V; Korecky, B; Vetter, R (The American journal of physiology, 1998)
Thyroid hormone (TH) levels increase in the postnatal life and are essential for maturation of myocardial Ca2+ handling. During this time, the sarcolemmal (SL) Na+/Ca2+ exchanger (NCX) function decreases and the sarcoendoplasmic reticulum (SR) Ca2+-ATPase (SERCA2) function increases. We examined the effects of postnatal hypo- or hyperthyroidism on NCX and SERCA2 in rat hearts. Animals were rendered hypothyroid by 0.05% 6-n-propyl-2-thiouracil in drinking water given to nursing mothers from days 2 to 21 postpartum. Hyperthyroidism was induced by daily injections of 10 microg/100 g body weight of 3,3',5-triiodo-L-thyronine during this period. Ventricular steady-state mRNA and protein levels of NCX and SERCA2 were analyzed by Northern and Western blotting. These were compared with SL Na+ gradient-induced and SR oxalate-supported Ca2+ transports in isolated membranes. In hypothyroidism, NCX mRNA and protein were elevated by 66 and 80%, respectively, and SERCA2 mRNA and protein were reduced to 55 and 70%, respectively (P < 0.05 vs. euthyroid). Corresponding differences were observed in the respective Ca2+ transports. Conversely, reduced NCX (by 50%) and elevated SERCA2 (by 150%) activities were found in hyperthyroidism (P < 0.05). The levels of NCX and SERCA2 mRNA and protein were, however, unchanged in hyperthyroidism, indicating that functional changes are not due to altered NCX and SERCA2 expression. In this case, a decline in noninhibitory phosphorylated phospholamban is a likely explanation for the elevated SR Ca2+ transport. In conclusion, physiological TH levels appear to be essential for normal reciprocal changes in the expression and function of myocardial NCX and SERCA2 during postnatal development.
Keywords: genetická transkripce; Sarcoplasmic Reticulum; Membrane Proteins; messenger RNA; trijodthyronin; Transcription, Genetic; Ca2+-ATPasy; Calcium-Binding Proteins; pumpa pro výměnu sodíku a vápníku; Thyroid Gland; novorozená zvířata; Sodium-Calcium Exchanger; Triiodothyronine; Hypothyroidism; krysa rodu Rattus; Calcium-Transporting ATPases; zvířata; štítná žláza; Regression Analysis; potkani Wistar; Gene Expression Regulation, Developmental; Propylthiouracil; Animals, Newborn; hypotyreóza; RNA, Messenger; Rats, Wistar; sarkolema; Heart; propylthiouracil; proteiny vázající vápník; Hyperthyroidism; Rats; membránové proteiny; myokard; vývojová regulace genové exprese; Animals; sarkoplazmatické retikulum; Myocardium; hypertyreóza; regresní analýza; srdce; Sarcolemma